GeoChemPlot : a user friendly Python based program for plotting geochemical data (2017)
"We present a user-friendly Python based program compatible with both Windows and Macintosh for plotting geochemical data. This software comes from the necessity to have an easier program that produces high quality graphics for scientific papers and laboratories users. The GeoChemPlot software produces 50 different types of ternary, bi-variable and spider plots concerning the following categories: tectonic environment discrimination, major elements, minor elements and blank (user-defined) plots. The intention of this program is to give easy to use software for the international geochemical community in order to simplify the classification and interpretation of laboratory data." -- Tomado del Formato de Documento de Grado.